Impact of demographic dividend on economic growth in developing countries - Yaqoob, Mohammad; Bani, Yasmin; Ishak, Suryati; Rosland, Anitha (Thammasat University, 2024)
This study investigates the impact of demographic dividends on economic growth by employing the dynamic common correlated effect (DCCE) as a panel data estimation technique. The analysis encompasses 71 developing countries from 1980 to 2019, further divided into lower- and higher-income countries. This study found that the demographic dividend, measured as the ratio of the working-age group in the population, significantly and positively influenced the economic expansion of overall developing countries and lower-income countries; however, the demographic dividend has an insignificant effect on higher-income countries. The results further demonstrate that the young population has a significant negative impact, and the elderly population positively affects economic growth. In addition to that, the study also found that physical capital per capita is negative, while human capital and trade openness offer a favourable outcome for economic growth. These results underscore the potential benefits of demographic change in most developing countries. However, investment in developing human and physical capital can enhance and promote the favourable effect of the working-age population ratio, fostering rapid economic growth.